Erosion and corrosion of alumina refractory by ingot casting steels. Issue 5 (April 2016) - Fruhstorfer, Jens; Schöttler, Leandro; Dudczig, Steffen; Schmidt, Gert; Gehre, Patrick; Aneziris, Christos G.
Abstract: This study investigated the corrosion of alumina-based refractories by alloyed steels. The alumina crucibles were physically characterized. Four steels with varying casting temperature and alloy contents were melted under argon atmosphere and the contact angles measured. Post-mortem, X-ray diffraction, optical and scanning electron microscopy and energy-dispersive X-ray spectrometry were used to analyze the erosion and corrosion. The refractory properties did not affect erosion and corrosion. No infiltration occurred. The contents of oxygen and deoxidizing steel alloys influenced the corrosion and erosion of the matrix. Firstly, manganese reacted to manganese aluminate. Silicon followed—forming manganese alumosilicates. For highest casting temperatures (1580 °C) also mullite formed. At the steel–refractory-interface aluminum displaced the silicates, enhancing corrosion. Due to mismatching thermal expansions, spalling occurred for the steel 17CrNiMo76 respectively 1.6587 in which mullite formed. In the coarse fraction only chromium doped alumina formed.